2014
DOI: 10.15252/embr.201439267
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of actin filaments with FBAR protein pacsin2

Abstract: Two mechanisms have emerged as major regulators of membrane shape: BAR domain-containing proteins, which induce invaginations and protrusions, and nuclear promoting factors, which cause generation of branched actin filaments that exert mechanical forces on membranes. While a large body of information exists on interactions of BAR proteins with membranes and regulatory proteins of the cytoskeleton, little is known about connections between these two processes. Here, we show that the F-BAR domain protein pacsin2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…hBin1 and its BAR domain do not only bind to F‐actin, but also stabilize F‐actin in a depolymerization assays. This stabilization was also observed for pacsin2 at higher concentrations . In contrast to pacsin2, hBin1 binding to actin filaments could partly protect them from cofilin‐mediated disassembly.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…hBin1 and its BAR domain do not only bind to F‐actin, but also stabilize F‐actin in a depolymerization assays. This stabilization was also observed for pacsin2 at higher concentrations . In contrast to pacsin2, hBin1 binding to actin filaments could partly protect them from cofilin‐mediated disassembly.…”
Section: Discussionmentioning
confidence: 66%
“…The crosslinking was carried out as described in . Briefly, F‐actin and hBin1 (isoform 1) or dBAR were mixed at the indicated concentrations in 10 mM PIPES, 50 mM KCl, 2 mM MgCl 2 , pH 6.8 and incubated for 30 min, before adding the EDC crosslinker (1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide hydrochloride; Thermo Fisher Scientific) at a final concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the reported interaction between PICK1 and F-actin in vitro was found to be merely caused by unspecific, probably electrostatic, interactions (Madasu et al, 2015). Electrostatic interactions with F-actin have also been observed in recent in vitro reconstitution studies using actin and the F-BAR protein syndapin II (Kostan et al, 2014). It will be interesting to clarify whether BAR domain proteins use their curved, positively charged BAR domain interfaces for direct binding of actin or actin-related molecules such as those incorporated in the Arp2/3 complex, or whether their crosstalk with actin-filament-promoting factors under physiological conditions instead requires interactions between other domains, such as the SH3-domain-mediated interactions of syndapin or CIP4/Toca subfamily members with activators of the Arp2/3 complex.…”
Section: Box 3 the Gtpase Cyclementioning
confidence: 89%
“…The mechanism of how EHD2 regulates caveolae motility and its association with stress fibers remains to be identified. Pacsin2, which binds to EHD2 (Moren et al, 2012), could link caveolae to actin as it has been recently shown to directly interact with actin (Kostan et al, 2014) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%